Selectively UV-Blocking and Visibly Transparent Adhesive Films Embedded with TiO(2)/PMMA Hybrid Nanoparticles for Displays - Choi, Jin-Wook (Materials (Basel), 2020)
To simultaneously achieve the high visible transparency and enhance the ultraviolet (UV)-blocking performance of displays, inorganic–organic hybrid nanoparticles, comprising TiO(2) as a core and poly(methyl methacrylate) (PMMA) as a shell, were uniformly incorporated into the optically clear adhesive (OCA) used in the front of a display device. The highly refractive TiO(2) nanocore could selectively scatter UV rays, which degrade the display performance, owing to the differences in the refractive indices between the inorganic particles and PMMA matrix, thereby offering an improved UV protection property to the adhesive film. Moreover, the organic PMMA nanoshell maintained the high visible light transmittance of the pristine OCA film via the prevention of particle agglomeration. To examine the effect of the PMMA nanoshell and nanoparticle size on the optical properties of the adhesive films, the OCA films embedded with only TiO(2) nanoparticles or hybrid nanoparticles with different particle sizes were prepared using a roll-to-roll process, and characterized in the range of UV and visible lights using UV-visible spectroscopy. It is experimentally revealed that the adhesive film including small TiO(2)/PMMA hybrid nanoparticles at an extremely low content exhibited enhanced UV-blocking properties and increased visible light transmittance compared to that with only TiO(2) nanoparticles.